Pengaruh Metode Concept Sentence terhadap Kemampuan Menulis Puisi Siswa Kelas X SMK Negeri 11 Medan - Putri Luthfiyah Ritonga; Salmah Naelofaria (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to analyze the effect of the Concept Sentence method on the poetry writing skills of tenth-grade students at SMK Negeri 11 Medan. This research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The sample consisted of 67 students, including 34 students in the control class and 33 students in the experimental class, selected through cluster random sampling. Data were collected using a poetry writing performance test assessed based on theme suitability, imagination, diction, figurative language, and imagery. Data analysis was conducted using descriptive and inferential statistics with IBM SPSS Statistics version 23, including normality, homogeneity, and Independent Samples t-test. The findings revealed that the experimental class achieved a higher mean score (78.48) than the control class (56.47). The Independent Samples t-test indicated a significance value below 0.05, demonstrating that the Concept Sentence method had a significant effect on students' poetry writing skills. These findings indicate that the Concept Sentence method effectively enhances students' ability to generate ideas, select appropriate diction, and compose poetry systematically. Therefore, this method can be considered an alternative instructional strategy for improving poetry writing skills in vocational high schools.